PR Toxin – Biosynthesis, Genetic Regulation, Toxicological Potential, Prevention and Control Measures: Overview and Challenges - Dubey, Manish K.; Aamir, Mohd; Kaushik, Manish S.; Khare, Saumya; Meena, Mukesh; Singh, Surendra; Upadhyay, Ram S. (Frontiers in Pharmacology, 2018)
Out of the various mycotoxigenic food and feed contaminant, the fungal species belonging to Penicillium genera, particularly P. roqueforti is of great economic importance, and well known for its crucial role in the manufacturing of Roquefort and Gorgonzola cheese. The mycotoxicosis effect of this mould is due to secretion of several metabolites, of which PR toxin is of considerable importance, with regard to food quality and safety challenges issues. The food products and silages enriched with PR toxins could lead in to damage to vital internal organs, gastrointestinal perturbations, carcinogenicity, immunotoxicity, necrosis, and enzymes inhibition. Moreover, it also has the significant mutagenic potential to disrupt/alter the crucial processes like DNA replication, transcription, and translation at the molecular level. The high genetic diversities in between the various strains of P. roqueforti persuaded their nominations with Protected Geographical Indication (PGI), accordingly to the cheese type, they have been employed. Recently, the biosynthetic mechanism and toxicogenetic studies unraveled the role of ari1 and prx genes clusters that cross-talk with the synthesis of other metabolites or involve other cross-regulatory pathways to negatively regulate/inhibit the other biosynthetic route targeted for production of a strain-specific metabolite. Interestingly, the chemical conversion that imparts toxic properties to PR toxin is the substitution/oxidation of functional hydroxyl group (-OH) to aldehyde group (-CHO). The rapid conversion of PR toxin to the other derivatives such as PR imine, PR amide, and PR acid, based on conditions available reflects unstability and degradative aspects. Since the PR toxin-induced toxicity could not be eliminated safely, the assessment of dose-response and other pharmacological aspects for its safe consumption is indispensable. The present review describes the natural occurrences, diversity, biosynthesis, genetics, toxicological aspects, control and prevention strategies, and other management aspects of PR toxin with paying special attention on economic impacts with intended legislations for avoiding PR toxin contamination with respect to food security and other biosafety purposes.